(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Each culture can blend a sort of architecture that can go from points of interest to regular homes. History has demonstrated that the different Architecture styles have created in light of atmosphere, way of life, topography and geology of a place, religious theory of the general population and accessibility of building materials. Religion and way of life appear to be the most well-known impacts in general. Culture, actually, underlines the critical part that financial matters, legislative issues, religion, legacy and the regular habitat play in forming the assembled condition. Kerala (the southern-most territory of India), the place where there is temples seems remarkable in this setting as the temples here were the rotate of religious, social, monetary and social existence of each Keralite. The common Hindu temples of Kerala emerge from among the Indian temple typology in its frame, auxiliary lucidity, complex convention, imagery or more all, in its development and craftsmanship in wood. They demonstrate a particular style which is a nearby adjustment of the Dravida or the South Indian convention of temple development, impressively affected by the different topographical, religious, social and political elements. A large portion of the temples of Kerala are generally neighborhood foundations of love, wealthy in both unmistakable and elusive social qualities. The spatiality of Kerala temples takes after the general Indian philosophical ideas of the inside, hub and the human relatedness to astronomical reality, while its execution in the fabricated frame takes after the Vedic religious practices. This paper endeavors to investigate the advancement of the non-specific fabricated type of temples of Kerala and the philosophical and spatial ideas of their architecture.